Regulatory T Cells and Clinical Application - Jiang, Shuiping (Springer, 2017)
Regulatory T-cell population is now widely accepted as an important component of the immune system as professional suppressors of immune responses. It was shown in the late sixties that some CD4+ T cells in normal mice were capable of suppressing autoimmunity. Efforts to characterize this autoimmune-suppressive CD4+ T cell population led to the identification of CD25 as a constitutional marker. Using this marker, it became possible to separate regulatory T cells from other CD4+ T cells, to further analyze their developmental pathways, especially in the thymus, and to better describe how they suppress immune responses in vivo and in vitro. The marker was also found to be useful to identify regulatory T cells with comparable suppressive function and phenotype in humans. It was recently shown that transcription factor Foxp3 was specifically expressed by CD25+ CD4+ regulatory T cells in rodents. Anomalies in FOXP3 gene are responsible for the development of an autoimmune and inflammatory disease in humans and rodents characterized by a deficiency in the development and function of CD25+CD4+ regulatory T cells. These recent findings provide clear evidence that Foxp3+CD25+CD4+ regulatory T cells are indispensable for the establishment and the maintenance of immunologic self-tolerance and immune homeostasis. Therefore, characterization of regulatory T cell mediated immune suppression should bring new clinical tools to control pathological immune responses.